System for time-resolved laser absorption spectroscopy and its application to high-power impulse magnetron sputtering - Adámek, P; Olejníček, J; Hubička, Z; Čada, M; Kment, Š; Kohout, M; Do, H T (The Review of scientific instruments, 2017)
This paper deals with the development and construction of an apparatus for time-resolved tunable diode laser absorption spectroscopy (LAS) for the diagnostics of pulsed plasma. A detailed description of the extension of a progressive method of laser absorption spectroscopy in continuous regime to a direct triggering method of the time-resolved laser absorption spectroscopy (TR-LAS) is presented. The main advantage of the developed method is its capability to measure the time evolution of the whole absorption profile with a preset time resolution, which can be less than 1 μs. Therefore, the presented method of repetitive sampling applied on LAS in plasma processes is capable of simultaneous measurement of the density and kinetic temperature of selected particles. Its appropriate applications are to periodical processes in technological plasma, namely pulsed plasma discharges. The developed method of TR-LAS was applied to measurements of the temporal evolution of density and kinetic temperature of argon metastable species during high-power impulse magnetron sputtering of titanium and titanium dioxide thin films.